Characteristics of the Croatian anchovy purse seiner fleet - Soldo, Alen (Array, 2019)
Croatia has a fishing fleet of 7559 vessels. Of these, small-scale coastal fishing boats, less than 12 meters in length, makes up 95,7% of the fleet. However, the largest percentage of catches, more than 94%, is made by purse-seiners that are representing only 3% of total fishing vessels. These vessels target small pelagic fish, predominately sardine and anchovy. This paper describes all the technical characteristics of the Croatian purse seiner fleet, based on 113 purse seine vessels registe-red in 6 Croatian ports and targeting anchovy in order to allow a precise determination of that fleet fishing capacity and subsequent management of the fleet in a responsible and sustainable manner. Comparison of different technical characteristics showed that the length of a vessel corresponds to the amount of the catch as well as to size of the fish. Hence, results confirm superiority of sonar, as a fish-finding device, over sounder in detecting fish shoals, which is prerequisite for purse seine fishing.